Telesna vadba žensk po porodu - Prevodnik, Eva (Šport (Ljubljana), 2024)
The purpose of this research is to study the degree of awareness and knowledge about postpartum exercise, which has been shown to have several positive effects on the recovery, lifestyle, and self-image of women. This study used an online questionnaire 1KA with postpartum women as its population (n=575). Data analysis was conducted in IBM SPSS software program. The most common deciding factors to perform physical activity postpartum were found to be good well-being, better self-image, more energy, and loss of body mass. On the other hand, the aspects that present the biggest obstacle to perform physical activity were fatigue, lack of time due to the new role, and the presence of pain. Moreover, the most common problems that affect women postpartum were back pain, diastasis recti, and urinary incontinence. The decision to be physically active was most commonly made six weeks postpartum, right after the first check up. Physical activity was most commonly characterized as taking the baby on a walk and performing exercises to strengthen pelvic floor. In general, women postpartum knew about and correctly performed exercises to strengthen pelvic floor. However, they found most of the information about basic exercises postpartum on the internet and they received the least amount of information from the gynecologist office prior to giving birth. Lastly, physical activity positively affected the quality of life in women postpartum.
Keywords: exercise; mental health; nosečnost; obdobje po porodu; physical activity; poporodno obdobje; postpartum period; pregnancy; sport; šport; telesna dejavnost; telesna vadba